PEMANFAATAN PENGEMBANGAN JARINGAN GAS BUMI SEBAGAI PENGGANTI LPG RUMAH TANGGA DI KABUPATEN BOJONEGORO-JAWA TIMUR - Andriawan; Rahmat Budiman; Dwijaya Febriansyah (Fakultas Teknik Universitas Pancasila, 2020)
This study was purposed to determine the cost saving obtained by household respondents from utilization of natural gas network development which will be installed replacing LPG uses in Bojonegoro regency. All 4,000 respondents still using Liquified Petroleum Gas (LPG) as fuel. Most of the respondents (93%) using LPG 3 kg (subsidy), 6% LPG 12 kg and 1% LPG 5.5 kg for their household needs. Commercially, cost savings obtained from natural gas network development instead LPG 3 kg is Rp 878,-/bottle, LPG 5.5 kg Rp 71,277,-/bottle and LPG 12 Rp 76,913,-/bottle. The average amount of natural gas per house is 12.39 m3/month. Total gas demand for 4,000 household respondents is 0.062 mmscfd and for all households in Bojonegoro regency is 6.48 mmscfd.